(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: Social Media has become a prevalent platform for students to receive information content such as admission notices, holiday notices from business schools. Students are communicating, collaborating, and resource sharing by several social media in the names of support groups. Objective: The purpose of the research paper is to examine social media adoption intention among undergraduate students of business schools in Kathmandu Valley in 2020. Method: The data were collected with the self-administered questionnaires from 200 undergraduate students. Partial Least Square (PLS) - SEM was applied to test the direct and mediated effect of the proposed hypotheses. Result: The results revealed that perceived ease of use, perceived usefulness, collaboration, resource sharing, communication and intention of social mediation adoption. Perceived ease of use partially mediates the relationship between communications, resource sharing on the intention of social media adoption. Conclusion: The study concludes that undergraduate level students of business schools could intent to social media when they find the social media useful, easy to use, collaborative, communication, and resource sharing among students. Moreover, students could intend to use social media when they perceived ease of social media use over communication, resource sharing for educational purposes. The conclusion could provide information for business schools in creating an atmosphere of collaboration, communication, and resource sharing to increase engagement in social media. Originality: Social media adoption in the Nepali context is a relatively less explored phenomenon. This research established that social media adoption is impacted by collaborative learning, resource sharing, perceived usefulness, and communication.